Modeling of Lithuanian cohort survivorship - Mišeikytė, Rasa (Lietuvos matematikos rinkinys, 1998)
Survival distributions, arising from six parametrical families were fitted to the mortality experience of Lithuanian cohorts, born in 1928–1935 and 1946–1966 years.